Energy efficiency analysis of converter-fed induction motors - Mushenya, John (Department of Electrical Engineering, 2019)
Electric motor systems are the largest consumers of industrial electrical energy. As Variable Speed Drives continue to dominate various industrial processes, there is need for stakeholders to fully understand and quantify the converter-fed motor losses over a wide range of operating conditions. Such knowledge is crucial for both manufacturers and end-users in performing energy-efficiency optimizations for motor-drive applications. Although there is an increase in legislative activities, particularly in Europe, toward classification and improvement of energy efficiency of electric motor-drive systems, the available standards for quantifying the various losses are still in their early stages of development. None of these standards have yet passed through all the required phases for them to be considered full international standards, owing to a lack of consensus on many technical issues. Therefore, the need for researchers to provide feedback to the relevant standards committees cannot be over-emphasized. One of the most challenging issues in estimating the efficiency of converter-fed motors is the accurate determination of additional harmonic losses due to the PWM voltages and currents. Although the recently introduced IEC 60034-2-3 Technical Specification has proposed a method of determining these losses through experimental testing, the approach is still undergoing validation. Moreover, it only considers the rated motor frequency and voltage whereas induction motor drives are usually operated over a wide range of speed and torque. The main emphasis of the work presented in this dissertation was to develop a thorough understanding of various converter-fed induction motor losses, and hence efficiency, when fed from a 2-level Voltage Source Inverter. In particular, the dissertation provides a healthy questioning of some concepts in the proposed IEC method, with a view to providing useful feedback for improving the standard. Comparisons are also drawn between the related standards to identify areas for improvement. This study further attempts to explain some conflicting reports cited in literature regarding the nature of additional harmonic losses. The experimental results obtained by testing three induction motors demonstrate some of the technical issues associated with the determination of additional harmonic losses. To mitigate the adverse effect of varying technical skill and competence levels on efficiency test results, an automated testing procedure was developed and implemented on the 110kW test rig in the UCT Machines Lab. The test rig, which boasts of a Genesis 7i high-speed Data Acquisition System, also provides an energy-efficient platform for investigating the steadystate and dynamic characteristics of converter-fed motors. By utilizing the capability of the Data Acquisition System to segregate the fundamental and harmonic components of measured input electrical power, it was found that a PWM power supply can be used in place of a conventional Variac to estimate the sinusoidal supply efficiency of an induction motor. This is a welcome development for both laboratory and field efficiency testing applications.